Narratives of Class in New Irish and Scottish Literature From Joyce to Kelman, Doyle, Galloway, and McNamee - McGlynn, M.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2008)
This book argues that the outskirts of cities have become spaces for a new literature beyond boundaries of traditional notions of nation, class, and gender. Includes discussions of Booker Prize winners Roddy Doyle and James Kelman.
Keywords: British literature; Literature, Modern—20th century; Literature—Philosophy.; Culture—Study and teaching; Fiction; British and Irish Literature; Twentieth-Century Literature; Literary Theory; Cultural Theory; Fiction